New Directions for American Policy in Asia (Czech Journal of International Relations, 1992)
Changes in the politics of the world's great powers continents, regions and individual countries much attention was paid to the species. At one o'clock of such changes, that is, about the change of American politicians see Asia, Bernard's book discusses K. Gordon.' The publication consists of a short introduction, some comprehensive chapters and the conclusion. In the introduction, the author notes that we are on the beginning of a new era in international politics, when ways of politics from the time after the Second World War cylinders can no longer be claimed. Created new ones American policies, especially the formulation of their principles, are also primarily focused on East Asia (hereafter referred to as VA) - however, it is not more precisely defined geographically - somehow the most dynamic area of ​​the world. With developments in this area, the USA must keep up without destroying the favorable conditions that helped to create. Due to the changes in the VA, the USA should formulate a new soy policy for the entire Asian continent.